Institutions as a lethal weapon: the case of Slovenia in the first wave of the Covid-19 epidemic - Flaker, Vito (Ревија за социјална политика/Journal of Social Policy, 2020)
The Covid-19 epidemic has most affected old people, not those who live at home – but those in old age homes. In Slovenia, as many as four-fifths of those deceased in the epidemic were residents of these institutions. The analysis shows that the essential moment of infection is institutionality, not age, that it is in this sense almost an institutional epidemic. The make-up of total institutions presents a significantly higher risk of transmission of infection – due to increased human concentration and increased frequency of contacts, but also because of the institutional structure and ethos, which objectify residents and deprive residents of the power of action. The deceased residents can be seen as (passive) victims not only of the virus, but also of the institutional nature of the organisation of care (prevailing in Slovenia). This was neglected in the debate so far, the measures introduced did not allow transfer to community care, which would provide residents with the level of safety comparable to the population at large, such services allowing a greater degree of self-isolation and control of contacts. The deceased residents are victims of a delay in deinstitutionalisation and in introduction of a potent, community based long-term care. These are the pressing tasks for the future, if we are to ensure at least safety for old people, and with it a life worth living.